Readiness of Technical University Students to Entrepreneurship Activity - M. G. Minin; E. V. Politsinskaya; V. G. Lizunkov (Высшее образование в России)
The article raises the problem of the formation of entrepreneurial competencies in response to the current situation in the country’s economy, which arose due to the lack of specialists capable of organizing innovation and technology business in the Territories of advanced socio-economic development (TOSED).The authors have analyzed the professional preferences of graduates of the National Research Tomsk Polytechnic University (Russia), the University of Zagreb (Croatia), and the University of Lyon (France) and identified the reasons why graduates do not create their own business. In order to determine the necessary cluster of entrepreneurial competencies of university graduates with basic technical education, a survey involving the representatives of Russian and foreign companies working in Russia, including TOSED residents, was conducted. As a result, the authors have received a list of key entrepreneurial competencies necessary for entrepreneurial activities and the formation of graduate competence in the field of management and business.The authors believe that for the formation of entrepreneurial competence, certain conditions must be created in the educational process for preparing a student for entrepreneurial activities, in particular a number of disciplines (entrepreneurship, technological entrepreneurship, project management, business planning) should be included in the curricula; interactive design training methods aimed to develop graduate’s readiness to create their own business should be applied. It is also necessary to provide an the interaction between universities and business structures, which are mostly the residents of TOSED.